The effect of STEAM-oriented wayground on motivation and problem-solving in elementary math - Ria Yuli Permatasari; Achmad Buchori; Ngatmini (Indonesian Journal of Educational Development (IJED), 2026)
The low learning motivation and problem-solving ability of elementary students remain significant challenges in Indonesian mathematics education. This study examines the effect of STEAM-oriented Wayground media on both variables among fourth-grade students on the flat shapes topic. A quantitative quasi-experimental pretest-posttest control group design was employed. The sample consisted of 46 students selected using purposive sampling, divided into an experimental group (n=26) receiving STEAM-oriented Wayground instruction and a control group (n=20) receiving conventional instruction. Instruments included an ARCS-based motivation questionnaire (16 items) and a Polya-based problem-solving test (20 items), both validated and reliable (Cronbach's Alpha 0.86 and 0.89). Data were analyzed using independent t-test and MANOVA. Results showed a significant effect on learning motivation (t = 10.662; p < 0.001) and problem-solving ability (t = 12.894; p < 0.001) compared to conventional learning. MANOVA also indicated a significant simultaneous effect (F = 165.468; p < 0.001; η² = 0.885). The experimental group showed moderate to high improvement (N-Gain motivation = 0.53; N-Gain problem-solving = 0.64). This study recommends integrating interactive digital media with a multidisciplinary approach as an innovative learning alternative in areas with limited resources.